Financial Performance on Climate Change Disclosure in the Indonesian Capital Market - Wulan, Diajeng Fitri; Wisesa, Panca; Ladista, Rindy Dwi (Jurnal Ilmiah Akuntansi & Bisnis, 2025)
Financial performance and climate change disclosure (CCD) in Indonesia Stock Exchange-listed enterprises are examined in this research. The study population contains 388 publicly listed firms from diverse industries to reflect the market. Random sampling minimized selection bias by giving each business an equal chance to be included in the research. Our independent variable, financial success, is assessed by return on assets (ROA), which shows how well a company makes money from its assets. CCD, the dependent variable, is assessed using the Task Force on Climate-related Financial Disclosures (TCFD) framework, which covers governance, strategy, risk management, and climate change indicators and objectives. ROA and CCD are examined using linear regression analysis to see whether enterprises with better financial situations are more inclined to declare their environmental practices. Financial success is positively and statistically significantly correlated with climate disclosure. This suggests that profitable corporations may invest more in non-financial reporting, especially climate risk and opportunity reporting. Financially strong firms may also disclose more climate-related information to boost corporate legitimacy, stakeholder confidence, and long-term commitment to sustainable business practices in response to rising global environmental expectations.